Application Of Importance Performance Analysis (IPA) Of Sapta Pesona Beach Marina Semarang - Dhameria, Vita; Sulfiani, Sulfiani; Kusumah, Adie Irwan (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2023)
This study aims to analyze the level of visitor satisfaction on the service performance of Marina Semarang beach. The method of measuring visitor satisfaction uses the IPA (Importance-Performance Analysis) method or the Performance Interest Analysis and the Customer Satisfaction Index or Customer Satisfaction Index (IKP). Data was collected by filling out questionnaires and interviewing 440 respondents who were visitors to Marina Semarang Beach who were domiciled in Semarang. The questionnaire consists of 3 parts: first, visitor characteristics data, second assessment/perception of visitors about the performance (performance) at the tourist attractions Marina Semarang Beach, third assessment/perceptions about the importance (importance) in tourist attractions Marina Beach Semarang. A total of 274 respondents or 62.27%, this shows that the respondents are satisfied, meaning that the implementation of the attributes of Sapta Pesona Marina Beach Semarang is satisfactory. a total of 437 respondents or 99.3%, this shows that respondents feel it is important that the implementation of the attributes of Sapta Pesona Marina Beach Semarang is expected to be improved.